PENGEMBANGAN MULTIMEDIA PENGURANGAN RISIKO BENCANA (PRB) BERBANTUAN MACROMEDIA FLASH BAGI SISWA SD DI WILAYAH RAWAN BENCANA - Dholina Inang Pambudi (Universitas PGRI Yogyakarta, 2015)
Abstract This study is a research and development with research subjects consisted of one person matterexperts, two media experts, elementary students. Data collection instrument in the form of sheet materialand expert validation for media experts, a questionnaire to students. Furthermore, the data obtained wereprocessed and analyzed using descriptive statistics as material for revision of the product to be eligible touse for testing in the field so that later could be used as a viable medium used for elementary students. Theresults obtained from research and development are; Multimedia disaster risk reduction is consideredfeasible to use as a learning resource based on the assessment of expert judgment matter experts, mediaexperts, and limited testing on students. Based on expert assessment criteria of the material included in thecategory of